Modeling Of A Stereo Vision System Using A Genetic Algorithm Based Fuzzy Linear Regression. - Hiaw, San Kho; Chee, Peng Lim; Abdul Aziz, Zalina; Abu Hassan, Anwar Hasni (2007)
In this paper a fuzzy linear regression (FLR) model integrated with a genetic algorithm (GA) is proposed. The proposed GA-FLR model is applied to modeling of a stereo vision system.